Phytohormones and Abiotic Stress Tolerance in Plants - Khan, Nafees A.; Nazar, Rahat; Iqbal, Noushina; Anjum, Naser A. (Springer Berlin Heidelberg : Imprint: Springer, 2012)
Plants are sessile and prone to multiple stresses in changing environmental conditions. Of the several strategies adopted by plants to counteract the adverse effects of abiotic stress, phytohormones provide signals to allow plants to survive under stress conditions. They are one of the key systems integrating metabolic and developmental events in the whole plant and the response of plants to external factors, and are essential for many processes throughout the life of a plant, influencing the yield and quality of crops. This book summarizes the current body of knowledge on crosstalk between plant stresses under the influence of phytohormones, and provides state-of-the-art information on recent developments in understanding the role of phytohormones and abiotic stress tolerance in plants. It further provides information on how modulation in phytohormone levels affects the regulation of biochemical and molecular mechanisms.